PEMAKNAAN SISWA SMA TERHADAP PUNISHMENT YANG DIBERIKAN GURU DISEKOLAH : STUDY INDIGENOUS PSYCHOLOGY - Deninta, Silva Dwi; Adri, Zakwan (CV. Causalita Dynamic Solutions, 2023)
Punishment is a treatment given to a person or group who makes a mistake or violates the rules that apply in the environment or agency. This study aims to find out how teachers treat students as punishment and how students understand the punishment given by teachers at school. With a total of 550 grade X high school students from Bukittinggi and Padang Panjang city areas, an original psychology approach was used in this study. Data was collected using the open-ended question method. The results showed that students usually dislike punishment given by teachers as they perceive it as negative. However, this is beneficial as it forces students to try better to avoid things that may allow them to receive punishment. Teachers should be more aware that punishment can improve students' behaviour without harming their physical and mental health.